AN ANALYSIS OF AMBIGUITY AND VAGUENESS IN ENGLISH JOKES ON SOCIAL MEDIA - Khamlue, Poramat; Sathientharadol, Phitsinee (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2020)
The objectives of this research are to analyze language patterns in English jokes found on social media and to compare the patterns in which English jokes are used the most. The researchers collected jokes data from social media such as Facebook, Instagram, and Twitter, selecting the 1,000 jokes with more than 10,000 likes, 1,000 shares or 1,000 comments from 16–22 December 2019 by using the concept of vagueness and ambiguity to analyze the data. The research results found that 48% of English language jokes were generated from vague language, 46% are generated by ambiguous language, and 6% from other forms of language.